Extraction of Association Rules in between Socio-demographics and Biochemistry Datasets of Schizophrenia Patients using Multi-Objective Genetic Algorithms - Kaya, Buket; Turkoglu, Ibrahim (Ios Press, 2013)
This paper presents a method for extracting automatically association rules via multi-objective genetic algorithms. The paper also proposes a novel objective measure to quantify the comprehensibility of the rules. The other objectives of the rules are average support value and average confidence value. We experimentally evaluate our approach on socio-demographics and biochemistry datasets of schizophrenia patients and demonstrate that our algorithm encourages us to improve and apply this strategy in many real-world applications.
9th International Conference on Intelligent Environments (IE) -- JUL 16-19, 2013 -- Athens, GREECE
Keywords: Data Mining; Association Rules; Multi-Objective Genetic Algorithms